Acute and long-term weight loss and weight gain in elite athletes: influences on body composition and performance - Garthe, I. (2011)
Many athletes attempt to change their weight in order to enhance their competitive performance level. Weight loss is generally motivated by a desire to optimise performance by improving power to weight ratio, making weight in order to compete in a certain weight category, or due to aesthetic reasons in sports that emphasise leanness. Weight gain is generally motivated by a desire to optimise performance by increasing muscle mass and thereby improving strength and power. Due to the negative effects of rapid weight loss and longer periods of restricted energy intake, existing literature recommends a gradual weight loss through moderate energy restriction and promotes a weekly weight loss of 0.5-1 kg. The same theoretical recommendation exists for weight gain; a moderate energy surplus for a gradual weight gain corresponding to a weekly weight gain of 0.5-1 kg. However, although recommended, the effect of such a weekly weight loss or gain on body composition and performance in elite athletes has not been examined. Further, the long-term effect on body composition and performance of such interventions is yet to be investigated.